2018
DOI: 10.1615/critrevbiomedeng.2018026019
|View full text |Cite
|
Sign up to set email alerts
|

Automation of Detection of Cervical Cancer Using Convolutional Neural Networks

Abstract: Classification of digital cervical images acquired during visual inspection with acetic acid (VIA) is an important step in automated image-based cervical cancer detection. Many algorithms have been developed for classification of cervical images based on extracting mathematical features and classifying these images. Deciding the suitability of a feature and learning the algorithm is a complex task. On the other hand, convolutional neural networks (CNNs) self-learn most suitable hierarchical features from the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…We used 50 × 50 pixels for the images of blastocysts. Only 15 × 15 pixels are used to detect cervical cancer . In a colposcopy study, it was reported that the accuracy for images of 150 × 150 pixels was better than that for 32 × 32 or 300 × 300 pixels, although images of uterine cervical lesion, including white epithelium and punctuation, seemed to be more complicated than images of blastocysts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used 50 × 50 pixels for the images of blastocysts. Only 15 × 15 pixels are used to detect cervical cancer . In a colposcopy study, it was reported that the accuracy for images of 150 × 150 pixels was better than that for 32 × 32 or 300 × 300 pixels, although images of uterine cervical lesion, including white epithelium and punctuation, seemed to be more complicated than images of blastocysts.…”
Section: Discussionmentioning
confidence: 99%
“…Only 15 × 15 pixels are used to detect cervical cancer. 93 In a colposcopy study, 67 it was reported that the accuracy TA B L E 4 Coefficients of the logistic regression, y = 1/ (1 + Exp(β 0 +β 1 x)), showing the probability of live birth as a function of the confidence score, which is the AI-generated predicted probability of live birth obtained from an image of the blastocyst When the AI system we made is applied to clinical use, the confidence scores could be used to select better blastocysts among all blastocysts according to the value. However, it is recommended that the regression function, which was applied to the data distribution of the patients, as shown in Figure 4 and Table 4, should be used to estimate the probability.…”
Section: Discussionmentioning
confidence: 99%
“…Such a large number of datasets for each age category will improve the value of AUC, sensitivity, specificity, and accuracy of the classifier with deep learning. It is also considered to investigate the image size, the appropriate number of training datasets, the appropriate timing after insemination to capture images, and the regularization values for further study to improve the accuracies and to avoid overfitting that is an error that occurs when a classifier is too fit to a limited set of data. It would be better to study other parameters, such as information of time lapses regarding their potential to predict live birth.…”
Section: Discussionmentioning
confidence: 99%
“…Image information is one of the parameters that need to be investigated. Only 15×15 pixels are used to detect cervical cancer (72). In a colposcopy study (61), it was reported that the accuracy for images of 150×150 pixels was better than those for 32×32 or 300×300 pixels.…”
Section: Discussionmentioning
confidence: 99%